The Happy prince - Potterton Productions; Shostale, Murray; Mills, Michael; Plummer, Christopher; Hiltz, James; Reader's Digest Association (Santa Monica : Released by Pyramid Films, 1973)
An animated film which presents and adaptation of Oscar Wilde's story of the Happy prince
Title from title screen
Animation, James Hiltz ; music, Ron Godwin
Narrators, Christopher Plummer, Glynis Johns
Keywords: Fairly tales -- Juvenile films; Children's films